Donor-Specific Anti-HLA Antibodies in Allogeneic Hematopoietic Stem Cell Transplantation - Morin-Zorman, Sarah; Loiseau, Pascale; Taupin, Jean-Luc; Caillat-Zucman, Sophie (Frontiers in Immunology, 2016)
Allogeneic Hematopoietic Stem Cell Transplantation (AHSCT) is a curative treatment for a wide variety of hematological diseases. In 30% of the cases, a geno-identical donor is available. Any other situation displays some level of Human Leukocyte Antigen (HLA) incompatibility between donor and recipient. Deleterious effects of anti-HLA immunization have long been recognized in solid organ transplant recipients. More recently, anti-HLA immunization was shown to increase the risk of Primary Graft Failure (PGF), a severe complication of AHSCT that occurs in 3 to 4% of matched unrelated donor transplantation and up to 15% in cord blood transplantation and T-cell depleted haplo-identical stem cell transplantation. Rates of PGF in patients with DSA were reported to be between 24 to 83% with the highest rates in haplo-identical and cord blood transplantation recipients. This led to the recommendation of anti-HLA antibody screening to detect Donor Specific Antibodies (DSA) in recipients prior to AHSCT. In this review, we highlight the role of anti-HLA antibodies in AHSCT and the mechanisms that may lead to PGF in patients with DSA, and discuss current issues in the field.